Intellectual property and digital trade: Mapping international regulatory responses to emerging issues - Wolf R. Meier-Ewert; Jorge Gutierrez (World Trade Organization (WTO), 2021)
This paper explores how regulatory responses to emerging IP issues in digital trade may develop at the international level and in particular how existing mechanisms might influence the chances of developing internationally agreed rules in this regard. The primacy of state sovereignty in intellectual property up to the late 19th century gave way to the important WIPO treaties, which still retained some independence of member states and based international regulatory responses directly on national experience. While more regulatory sovereignty was ceded in TRIPS, the WIPO Copyright Treaty and the WIPO Performances and Phonograms Treaty, the adoption of non-binding instruments (such as the WIPO Joint Recommendations in the area of trademarks) show the limits of decision making by consensus. International non-state solutions such as the Uniform DomainName Dispute-Resolution Policy (UDRP) established by the Internet Corporation for Assigned Names and Numbers (ICANN) have introduced separate, technically determined solutions to specific IP issues. Proliferating free-trade agreements (FTAs) have emerged as a new platform to agree to IPrelated regulatory responses that can be used to project the national solutions of a few dominant FTA-partners. However, these FTAs have also served to give legally binding status to internationally agreed non-binding recommendations. These diverse approaches are apparent in recent IPregulatory responses to emerging digital issues that are particularly relevant for digital business models, including inter alia Internet service provider (ISP) liability, "safe harbour" provisions and the issue of orphan works, where there appears to be less agreement. Still further behind to reaching any kind of agreement are the emerging issues of online exhaustion, data mining and IP-related questions of artificial intelligence.
Keywords: F13; K10; K33; O30; O31; O33; O34; 330; intellectual property; trade in knowledge; digital trade; TRIPS Agreement; Berne Convention; Paris Convention; WIPO Internet Treaties; Regional Trade Agreements; online exhaustion; safe harbour; ISP liability